High School National Examination and its implications for environmental science teaching - Santos, Luiz Ricardo Oliveira; Costa, Jailton de Jesus; Souza, Rosemeri Melo e (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The National High School Examination (ENEM) is a government policy instituted by the Ministry of Education with the aim of evaluating this teaching stage, also serving as an alternative to access the Higher Education at the main universities of the country, through programs such as the System Unified Selection (SiSU), the University for All Program (ProUni) and Student Funding (FiES). Despite the reformulations it has undergone lately, the exam creates obstacles that can imply teacher autonomy and teaching, compromising the local and integrated approach to environmental themes. The aim of the present study is to discuss the implications of ENEM for the Environmental Science teaching. For this, preliminary bibliographic data such as articles indexed in the CAPES database and documentaries were collected through the analysis of the Human Sciences and Nature Sciences tests applied in 2016, which proved the little approach to local environmental themes in that year, prevailing those of global and the most developed region of the country, contradicting the interdisciplinary proposal of the examination. Thus, it is observed that the ENEM rarely addressed local questions in its tests, and the school should use other pedagogical instruments to improve the effectiveness of Environmental Science Teaching.